2017
DOI: 10.1017/qua.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Holocene sea level and climate change from Almenara marsh (western Mediterranean)

Abstract: In the Almenara marsh (western Mediterranean), four cores were analyzed to establish the relationship between the marsh record of the Almenara marshlands and the environmental factors responsible for its evolution during the Holocene. One hundred and eighty-six samples were collected for sedimentologic and paleontological study: 63 for biomarker analysis; 5 for amino acid racemization (AAR) dating; and 5 for 14C dating. Litho and biofacies analyses identified distinct paleoenvironments, with the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
0
18
0
2
Order By: Relevance
“…In the Valencian gulf, the maximal inland position of the beach dated at 7500-7200 cal. BP (Carmona and Ruiz, 2011) has also been associated with the desiccation of several coastal lagoons (Marco-Barba et al, 2013;Blázquez et al, 2017). In very detailed sequences, this evolution has been constrained at 7700-7000 cal.…”
Section: Influence Of Climate On the Morphogenetic Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Valencian gulf, the maximal inland position of the beach dated at 7500-7200 cal. BP (Carmona and Ruiz, 2011) has also been associated with the desiccation of several coastal lagoons (Marco-Barba et al, 2013;Blázquez et al, 2017). In very detailed sequences, this evolution has been constrained at 7700-7000 cal.…”
Section: Influence Of Climate On the Morphogenetic Evolutionmentioning
confidence: 99%
“…(caption on next page) deltas (Anthony et al, 2014;Amorosi et al, 2013a), coastal barrier system constructions and large development of lagoon environments (Marco-Barba et al, 2013;Blázquez et al, 2017;Melis et al, 2017;Melis et al, 2018;Pascucci et al, 2018).…”
Section: Influence Of Climate On the Morphogenetic Evolutionmentioning
confidence: 99%
“…For most of the last 4000 years, coastal wetlands have no direct connection to the sea. In the case of the marshes of Almenara and Benicasim, the paleoecological studies (foraminifers and ostracods) show that they were oligohaline marshes only affected by small fluctuations in their water levels (Usera et al, 1996;Mediato, 2016;Blázquez et al, 2017Blázquez et al, , 2018Rodríguez-Pérez et al, 2018). These authors did not reach conclusive paleoecological data that allowed distinguishing relative changes in salinity of wetlands during the period.…”
Section: Introductionmentioning
confidence: 99%
“…They are typical features of the coastal plain landscapes of the Spanish Mediterranean coast: Mar Menor, Valencia lagoon, Oliva-Pego marsh, Almenara, Benicasim and Torreblanca-Cabanes marshes. Previous sedimentological, geomorphological and paleontological studies focused on their paleoenvironmental reconstruction during the Holocene (Dupré et al, 1988;Usera et al, 1996Usera et al, , 2002Mediato and Santisteban, 2006;Carmona and Ruiz, 2011;Marco-Barba et al, 2013, Carmona et al, 2016Mediato, 2016;Blázquez et al, 2017Blázquez et al, , 2018Rodríguez-Pérez et al, 2018;Ruiz-Pérez and Carmona, 2019;López-Belzunce et al, 2020). These studies concluded that the Holocene paleoenvironmental changes were related to the eustatic variations that took place since the Last Glacial Maximum and climate was a minor forcing of local interest.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años, han proliferado los estudios sobre el registro holoceno de medios costeros, con especial atención a la incidencia de los cambios climáticos y las fluctuaciones del nivel del mar sobre ellos (Cohen et al, 2016;Fanget et al, 2016;Araujo et al, 2017;. Sus resultados suelen basarse en el análisis pluridisciplinar de testigos continuos o secciones superficiales, que a menudo incluye la identificación de diatomeas o polen para poder deducir su evolución paleogeográfica y ambiental (Anderson, 2000;Leventer et al, 2010;Prieto et al, 2017;Blázquez et al, 2017;Quick et al, 2018).…”
Section: Introductionunclassified